Coastal wetlands of Victoria, south‐eastern Australia: providing the inventory and condition information needed for their effective management and conservation. Issue 4 (28th February 2014) - Boon, Paul I.; Allen, Tim; Carr, Geoff; Frood, Doug; Harty, Chris; Mcmahon, Andrew; Mathews, Steve; Rosengren, Neville; Sinclair, Steve; White, Matt; Yugovic, Jeff
Abstract The effective management and conservation of coastal wetlands requires an appropriate typology to underpin classification and mapping, adequate inventory information, and a robust assessment of ecological condition and threats. Extensive and floristically diverse coastal wetlands occur along much of the coast of Victoria (south‐eastern Australia), but there are serious deficiencies in all these information requirements. Previously unanalysed data from the Victorian Biodiversity Atlas were used to revise the typology currently applied to coastal saltmarsh in Victoria. To supplement the single unit currently used for State‐endorsed mapping and inventory (EVC 9 Coastal Saltmarsh Aggregate), seven new Ecological Vegetation Classes are proposed to better reflect the floristic and structural diversity of coastal saltmarsh in south‐eastern Australia. Coastal saltmarsh is currently allocated the lowest conservation status ('least concern') across much of Victoria, and it is recommended that this be upgraded variously to the higher categories of 'endangered', 'vulnerable', or 'rare'. A State‐wide inventory using the new typology, prepared using recently flown, high‐resolution aerial photographs and extensive ground‐truthing (212 person‐days), indicated that there were 19 212 ha of coastal saltmarsh of all types, 5177 ha of mangroves, and 3227 ha of EVC 10 Estuarine Wetland (a wetland type dominated by Juncus kraussii) in Victoria. On‐ground assessments undertaken across 30 geographic sectors of the coast indicated that coastal wetlands were confronted by a wide range of anthropogenic threats, which in many cases were quite different from those outlined in prior reviews of Australian wetland systems. Weed invasions were especially problematic, not so much of the exotic and highly publicized Spartina in the lower levels of tidal wetlands but from a wide range of exotic taxa in more elevated saltmarshes (e.g. tall wheat grass Lophopyrum ponticum). Copyright © 2014 John Wiley & Sons, Ltd.